2013
DOI: 10.1136/jnnp-2013-306203
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the incidence of ischaemic stroke in young adults between 1985 and 2011: the Dijon Stroke Registry

Abstract: Multiple factors may account for the increased incidence of ischaemic stroke in people aged <55 years including changes in vascular risk factors, better awareness of the disease and treatment options in the population and among practitioners leading to more frequent referrals for specialised care, and improvements in stroke diagnosis. Stroke prevention must be encouraged even in young adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
148
3
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(174 citation statements)
references
References 22 publications
17
148
3
6
Order By: Relevance
“…We suspect that there might have been a shift from major stroke and death to minor stroke and TIA, given that there is a national decrease in major strokes and deaths and younger patients present with minor stroke/TIA. Our results are in agreement with those of the Dijon Stroke Registry 15 and the Greater Cincinnati/ Northern Kentucky region, 16 both showing an increase in younger patients presenting with stroke. Improved stroke prevention strategies and stroke symptom awareness may be responsible for diagnosing minor stroke/TIA at a younger age in patients at risk.…”
Section: Bogiatzi Et Al Secular Trends In Stroke Subtypes 3211supporting
confidence: 82%
“…We suspect that there might have been a shift from major stroke and death to minor stroke and TIA, given that there is a national decrease in major strokes and deaths and younger patients present with minor stroke/TIA. Our results are in agreement with those of the Dijon Stroke Registry 15 and the Greater Cincinnati/ Northern Kentucky region, 16 both showing an increase in younger patients presenting with stroke. Improved stroke prevention strategies and stroke symptom awareness may be responsible for diagnosing minor stroke/TIA at a younger age in patients at risk.…”
Section: Bogiatzi Et Al Secular Trends In Stroke Subtypes 3211supporting
confidence: 82%
“…Moreover, the decreased incidence of ICH in elderly men may be associated with the unchanged prevalence of hypertension and the reduced frequency of smoking during 1991 to 2011. 29 Simultaneously, the 12-fold increased prevalence of diabetes mellitus and alcohol consumption and 2-fold increased prevalence of obesity in elderly women contributed partly to the increased incidence of ICH in this study. 29 Previous studies reported that there was a higher proportion of ICH among Chinese than among Caucasians.…”
Section: Discussionmentioning
confidence: 75%
“…29 Simultaneously, the 12-fold increased prevalence of diabetes mellitus and alcohol consumption and 2-fold increased prevalence of obesity in elderly women contributed partly to the increased incidence of ICH in this study. 29 Previous studies reported that there was a higher proportion of ICH among Chinese than among Caucasians. 4,20,21,26 However, we found that the incidence of ICH remained stable in young and middle-aged adults in the present study, but it decreased in those aged at least 65 years.…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…18 However, several studies have shown that the incidence of first-ever stroke in young and middle-aged adults increased in different races over the last 2 decades. 19,20 Authoritative statistics indicated that the mean age of people with stroke significantly increased from 73.9 years in 1990 to 74.5 years in 2010 in high-income countries and from 68.8 years in 1990 to 69.4 years in 2010 in low-income and middle-income countries. 3 Contrary to these previous studies, we found a dramatic increase in the incidence of first-ever stroke and a striking decrease in the mean age of stroke patients from 1992 to 2014 among a low-income population in China.…”
Section: Discussionmentioning
confidence: 99%